Dukungan Suami Dalam Penggunaan Metode Kontrasepsi Pada Perempuan Dengan Riwayat Pernikahan Usia Dini Di Desa Klampok, Kec. Singosari Kab. Malang - Khoirunisa, Nurhafidz; Bahari, Kissa; Yudianti, Ika (Poltekkes Kemenkes Jambi, 2024)
Marriage carried out by adolescents affects the high birth rate, women who marry under the age of < 20 years have a longer reproductive span so it is advisable to use contraceptives. One of the efforts to increase the scope of contraceptive use is husband support. Early marriage is rife in Indonesia, especially East Java Province, which ranks third in the highest number of early marriages in Indonesia after South Kalimantan and West Java with a percentage of 10.85% of the total 64,211 cases in 2020. Indonesia faces problems in the growth rate that is still high but the quality of health is still low so that government policies are held through family planning (KB) policies. This study aims to determine the picture of husband support in the use of contraceptive methods in women with a history of early marriage